Added Value of IP-10 as a Read-Out of Mycobacterium tuberculosis: Specific Immunity in Young Children. Issue 12 (December 2016) - Jenum, Synne; Dhanasekaran, Sivakumaran; Ritz, Christian; Macaden, Ragini; Doherty, T. Mark; Grewal, Harleen M. S.
Abstract : We have explored the added value of interferon-γ (IFNγ)–inducible protein 10 as a read-out of Mycobacterium tuberculosis –specific immunity in young Indian children, where the sensitivity of the IFNγ release assays for tuberculosis is poor. Reduced frequency of indeterminate results and an increased sensitivity for tuberculosis suggest a potential for fewer missed cases with a combined IFNγ/inducible protein 10 read-out in a 4th generation IFNγ release assays. Abstract : Supplemental Digital Content is available in the text.